Alterations in lipid peroxidation, lipid profile, insulin sensitivity, and hepatic histopathological changes in diabetic rats following the treatment with Salvadora persica. Issue 3 (30th September 2018) - Saeedi Borujeni, Mohammad Javad; Esfandiary, Ebrahim; Ghanadian, Mustafa; Valiani, Ali; Baradaran, Azar; Yazdani, Amid
Abstract: We examined the effects of various partitions of Salvadora persica extract on lipid profile (LP), lipid peroxidation, and insulin sensitivity (IS) of diabetic rats. The rats were divided into normal control, diabetic control (DC), standard, sham, and test groups. The test groups were treated with an oral dose of 200, 400, and 600 mg/kg of crude, aqueous, and ethyl acetate partition of S. persica extract. After 21 days of experiment, the fasting blood glucose (FBS), LPs, lipid peroxidation, IS, liver enzymes levels, liver histopathology, and body weight alteration were evaluated. A significant decrease in FBS and lipid profile (except HDL) were observed in rats treated with various dose of extract compared with the DC rats ( P  < 0.05). Treating diabetic rats with various extracts of S. persica meaningfully decreased the level of malondialdehyde ( P  < 0.05). Animals treated with various dose of aqueous extract showed better results ( P  < 0.01). On the basis of used indirect indexes to determine IS, all partitions of extracts showed anti‐insulin resistance effects in diabetic rats. On the basis of our statistical analyzing, treating diabetic rats with all of the three extracts of S. persica decreased the elevated levels of alanine phosphatase, aspartate aminotransferase, and alanine transferase. Also, pathological changes in the liver tissue were reduced following treatment with the S. persica . In conclusion, our results give evidence that the S. persica extract, especially aqueous partition, has a healing effect on diabetes and can be considered as an alternative therapy for this disease.